Strategic partnership models between businesses in East Africa - Oberoi, Zeena; Schun, Laura; Kropff, Wietske; Vyas, Shalika; Oroko, Jamleck; Peterson, Nathanial (2023)
This report investigates strategic partnerships in East Africa's agriculture sector, emphasizing the critical role of smallholder farmers (SHFs) in meeting rising demands. It explores the potential of collaborative models between primary companies (dealing in high-demand products) and secondary companies (offering specialized services like soil testing). The report aims to enhance understanding of co-opetition—a unique strategic partnership form—and examines various types of alliances, their advantages and disadvantages, behavioral mechanisms influencing success, and strategies for achieving effective collaboration. Through comprehensive literature review and case studies, the report seeks to provide insights and frameworks for growth, efficiency, and sustainability in East African agriculture, addressing key questions about strategic alliances, their types, and the potential for co-opetition in the region.